2020
DOI: 10.5530/ijopp.13.3.47
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular Drug induced Hepatitis: An Adverse Drug Reaction

Abstract: Antitubercular drugs are the first line agents for the management of tuberculosis. Drug induced hepatotoxicity is an unexceptional adverse effect mostly caused by antitubercular drugs leading to cessation of therapy. The keystone for the treatment of tuberculosis is a 6-month regimen consisting of drugs such as Isoniazid, rifampicin, pyrazinamide and ethambutol. Although Antitubercular drugs are only option for the treatment for pulmonary TB, Hepatotoxicity is one of the most detrimental adverse events leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although CYP2E1 c1/c1 was present in both the DILI and non-DILI groups, the genotypes C/D or C/C were three times more likely to result in anti-TB DILI. The same study showed that the risk of DILI went up when the NAT2 gene polymorphism was combined with the CYP2E1 C/D or C/C genotype [33,38,39].…”
Section: Mechanism Of Liver Injurymentioning
confidence: 88%
“…Although CYP2E1 c1/c1 was present in both the DILI and non-DILI groups, the genotypes C/D or C/C were three times more likely to result in anti-TB DILI. The same study showed that the risk of DILI went up when the NAT2 gene polymorphism was combined with the CYP2E1 C/D or C/C genotype [33,38,39].…”
Section: Mechanism Of Liver Injurymentioning
confidence: 88%
“…In rare cases, amikacin can also cause hepatitis or hepatitis. Blood tests that monitor levels of liver enzymes and bilirubin the red stains that form when red blood cells are removed diagnose liver disease [24].…”
Section: Figurementioning
confidence: 99%
“…According to World Health Organization (WHO), tuberculosis has been declared a global health emergency, with almost onethird of the world's population estimated to be infected. Directly observed treatment, short-course (DOTS) is the mainstay of tuberculosis treatment, according to the RNTCP (Begum, Parveen, Sultana, Fatima, & Fareedullah, 2020). The liver is the largest solid organ in the body as well as the largest gland.…”
Section: Introductionmentioning
confidence: 99%